Daily auricular stimulation with capsaicin ointment improved cough reflex sensitivity in elderly patients with dysphagia: a pilot study. (3rd March 2020) - Ohnishi, Hiroki; Jinnouchi, Osamu; Agawa, Seiji; Kondo, Eiji; Kawata, Ikuji; Okamoto, Hidehiko; Azuma, Takahiro; Sato, Go; Kitamura, Yoshiaki; Abe, Koji; Takeda, Noriaki
Abstract: Background: In our previous study, a single auricular application of capsaicin ointment, but not placebo improved cough reflex in elderly patients with dysphagia. Aims/Objectives: In the present study, we examined whether daily auricular application of capsaicin ointment continued to improve cough reflex in similar patients. Material and methods: With a cotton swab, 0.025% capsaicin ointment was applied in each external auditory canal alternately once a day for 2 weeks. The cough reflex sensitivity was evaluated on videoendoscopy using a numerical score and inhalation cough challenge test using citric acid in elderly dysphagic inpatients. Results: After daily auricular application of capsaicin ointment for 2 weeks, the endoscopic score of glottal closure and cough reflexes significantly improved, and the citric acid cough threshold significantly decreased. There was a significant correlation between the endoscopic score and the citric acid cough threshold before and after daily capsaicin application in the patients. Conclusions : Daily auricular stimulation with capsaicin ointment for 2 weeks continued to improve the cough reflex sensitivity in elderly patients with dysphagia. Significance: Daily auricular stimulation with capsaicin ointment would be a safe and effective intervention to prevent pneumonia in elderly with a risk of aspiration.